2019
DOI: 10.3904/kjim.2018.325
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunotherapy in multiple myeloma

Abstract: In multiple myeloma (MM), the impaired function of several types of immune cells favors the tumor's escape from immune surveillance and, therefore, its growth and survival. Tremendous improvements have been made in the treatment of MM over the past decade but cellular immunotherapy using dendritic cells, natural killer cells, and genetically engineered T-cells represent a new therapeutic era. The application of these treatments is growing rapidly, based on their capacity to eradicate MM. In this review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Immune dysfunction leads to MM tumor cell immune evasion, thereby promoting MM progression. Immune dysfunction includes the loss of immunogenicity against the malignant PC population via the immune editing upregulation of inhibitory ligands that promote immune tolerance and T-cell exhaustion as well as the development of an immunosuppressive tumor microenvironment that fosters tolerance and immune escape . Consistently, we noted that the differentially expressed proteins identified in our study showed predicted functions related to the modulation of apoptosis, programmed cell death, cellular protein metabolism, immunity and host defense responses, and growth signaling pathways.…”
Section: Discussionsupporting
confidence: 78%
“…Immune dysfunction leads to MM tumor cell immune evasion, thereby promoting MM progression. Immune dysfunction includes the loss of immunogenicity against the malignant PC population via the immune editing upregulation of inhibitory ligands that promote immune tolerance and T-cell exhaustion as well as the development of an immunosuppressive tumor microenvironment that fosters tolerance and immune escape . Consistently, we noted that the differentially expressed proteins identified in our study showed predicted functions related to the modulation of apoptosis, programmed cell death, cellular protein metabolism, immunity and host defense responses, and growth signaling pathways.…”
Section: Discussionsupporting
confidence: 78%
“…According to information available by Oncologia Brasil on its own website in the year 2019, the most prevalent average age of MM carriers was 63 years, being mostly male (VO et al. 2019).…”
Section: Introductionmentioning
confidence: 99%
“…MM is considered an incurable disease, but it is treatable. It is common that its carriers present modifications in the production of other blood cells, being observed alterations in the hemogram, such as anemia, thrombocytopenia and leukopenia (DOS SANTOS et al, 2022;VO et al, 2019;MILANI;FERNANDES, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the standard treatment strategy for MM is high-dose chemotherapy (such as carfilzomib, bortezomib and melphalan) followed by stem cell transplantation (if accessible), which effectively prolongs patient survival time (4). However, due to its complexity, MM remains a challenge to treat, and its precise pathogenic mechanisms have not been fully clarified (5,6). Therefore, it is important to determine the lncRNA transcription factor 7 is related to deteriorating clinical features and poor prognosis in multiple myeloma, and its knockdown suppresses disease progression by regulating the miR-203-mediated Jagged1-Notch1 signaling pathway underlying etiology of MM and to identify potential new treatment targets.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the standard treatment strategy for MM is high-dose chemotherapy (such as carfilzomib, bortezomib and melphalan) followed by stem cell transplantation (if accessible), which effectively prolongs patient survival time ( 4 ). However, due to its complexity, MM remains a challenge to treat, and its precise pathogenic mechanisms have not been fully clarified ( 5 , 6 ). Therefore, it is important to determine the underlying etiology of MM and to identify potential new treatment targets.…”
Section: Introductionmentioning
confidence: 99%